Coordination and variability of muscular activation in male athletes with and without subacromial impingement syndrome: A case-control study - Rahman Sheikhhoseini; Sajjad Abdollahi; Mohammad Salsali; Mehrdad Anbarian; Trent M. Guess (PLoS ONE, 2025)
Objectives Athletes with Subacromial Impingement Syndrome (SIS) exhibit altered muscular coordination and variability during repetitive shoulder movements compared to athletes without SIS. This research compared the Coordination and Variability of Muscular Activation in Male Athletes with and Without SIS. Methods In this case-control study, twenty-four male athletes were recruited and divided into two groups: those with SIS (n = 12) and those without SIS (n = 12). Participants performed a repetitive reaching task (RRT) for a minimum of fifteen repetitions. Electromyography (EMG) data were recorded from selected shoulder muscles. Muscle synergies, intra-group variability, and inter-group variability were extracted from the EMG data. An independent sample t-test or Mann-Whitney U-test was employed to analyze data at a significance level of 95% (α < 0.05). Results Three observable muscle synergy patterns were identified in both groups. Significant differences in variance accounted for (VAFmuscle) were found in the posterior deltoid, subscapular, and middle deltoid muscles, but these differences may not be clinically significant and warrant further research. No significant statistical differences were found in intra-group variability between the groups, which may suggest that the hypothesis is not fully supported. However, significant differences in inter-group variability were observed between the SIS and control (CON) groups. Conclusions This study showed differences in muscular coordination and variability during RRT in athletes with and without SIS. Three different muscle synergy patterns were demonstrated in both groups. It seems that timing and coordination changes in muscle activation may influence movement efficiency and increase the risk of performance errors.